Le sexe des difformités et la réponse orthopédique (1819-1862) - Grégory Quin (Genre & Histoire)
This article examines how gendered ideologies affected medical discourses concerning individuals with spinal deformities during the first half of the 19th century. The gradual recognition of sexual dimorphism among patients allows us to clarify the entanglement of medical and pedagogical theories that appears in the institutionalization of orthopaedics at this time and the emergence of physical education. The article begins by highlighting doctors’ approaches to the understanding of spinal deformities and diseases of the spine ; it then explores the different educational approaches elabored within private orthopedic and gymnastic institutions.